Individual differences and coping processes in explaining health symptoms in prisoners - Buško, Vesna (Array, 1996)
The study deals with an attempt at application of transactional stress and coping model to the analysis of the determinants of inmate adjustment to imprisonment. Relevant demographic, criminological and personality measures, some situational features, and mediating processes - cognitive appraisals and coping strategies, were taken in the sample of 475 males incarcerated in Croatian penal institutions of minimum, medium or maximum security level. Self-report psychosomatic problems scale was also administered as a short-term measure of inmate adjustment to the conditions of prison life. Relative predictive power of particular groups of individual, situational and mediating variables was estimated by hierarchical regression procedures, with the cognitive appraisal on event controllability taken as a moderator variable. Results showed that in the situation of low level of perceived controllability, all groups of predictor variables accounted for significant portion of criterion variance, whereas significant additive contribution in the group with high perceived controllability was found for personality dimensions and two sets of mediating processes variables. Total amount of variance in psychosomatic problems scores explained by the whole system of employed predictors was 60% and 69%, for the low and high event controllability groups, respectively. Findings support theoretical views on the mediating role of coping mechanisms, and the moderating role of perceived event controllability in establishing the relationships within the stress and coping model.